From participatory to inclusive climate services for enhancing societal uptake - David Samuel Williams (Elsevier, 2021)
Climate services are seen as key for informing decision-making and policy planning around climate change adaptation. However, recent research shows the current application of climate services in actual decision-making and policy planning on the ground still being limited. A common critique in the current development of climate services is their tailoring toward those users with sufficient capacity to adapt, as opposed to those most in need of adaptation. In an attempt to address this key limitation, citizens‘ assemblies are proposed in contributing to the inclusivity of climate services, enhancing their legitimacy and potential for societal uptake. After introducing the concept of climate services and limitations thereof, citizens‘ assemblies are presented along with a blueprint for designing inclusive climate services.